Subjektivitet i fortællinger - Larsen, Gorm (K&K - Kultur og Klasse, 2006)
Udsigelsens fortolkninger Subjectivity in Narratives: Interpretations of Enunciation An ongoing discussion in literary theory is about whether the narrative text generally, has narrator or not. The respectively positive and negative interpretations illustrate two paradigms in the narrative theory. Gorm Larsen shows that the two positions are connected by the concept of enunciation: Käte Hamburger and Émile Benveniste introduced the concept of enunciation and argued at the same time that only I-narratives have a structure of enunciation. In the view of poststructural theory this has been radicalised into a complete denial of the narrator. Gorm Larsen argues however that the different interpretations of enunciation are not in conflict with each other, but – from a narratological and structural point of view – a matter of different levels on which subjectivity in narrative can be understood; this shows that subjectivity in narrative is a complex state of affairs.